Application of Occupational Health and Safety Management through Job Safety Analysis in Steel Structure Installation: A Case Study of the P.T. Ultra Sakti Workshop Construction - Putra, Alfandias Seysna; Ramdan, Muhammad; Putri, Isria Miharti Maherni (Fakultas Teknik Universitas Tanjungpura, 2024)
Workplace accidents are a prevalent issue across various construction projects, including workshop development. To address this challenge, the implementation of Occupational Health and Safety (OHS) management is crucial. This study aims to evaluate the application of OHS management, with a focus on the utilization of Job Safety Analysis (JSA) methods to prevent workplace accidents during workshop construction projects. The research employs a qualitative field study approach. Data were collected through direct observations, interviews with workers, project managers, and Health, Safety, and Environmental (HSE) personnel, as well as through the analysis of relevant OHS documentation. The JSA implementation process was assessed at various stages, including hazard identification, control measure determination, and the implementation of preventive actions. The findings reveal that the average risk level associated with steel structure installation work is classified as moderate, with a percentage of 51%. Activities that present high to extreme risk levels are predominantly related to tasks performed at height, such as the installation of main beams, secondary beams, and rafters, with fall and impact hazards being significant concerns. To mitigate these risks, appropriate controls must be enforced, including the use of Personal Protective Equipment (PPE), full-body harnesses, effective housekeeping practices, and the installation of signage and the isolation of hazardous work areas. These measures can effectively reduce risk levels from high and extreme to low and moderate.